Chinese patent medicine tongxinluo capsule as a supplement to treat chronic coronary syndromes: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Shi-Bing Liang; Shi-Bing Liang; Shi-Bing Liang; Yi-Fei Wang; Yi-Fei Wang; Yi-Fei Wang; Zhen-Chao Niu; Zhen-Chao Niu; Yu-Fei Li; Hui-Min Zheng; Hui-Min Zheng; Jia-Ming Huan; et al. (Frontiers in Cardiovascular Medicine)
BackgroundChronic coronary syndromes (CCS) is a common clinical condition that increases the risk of cardiovascular events at any time. Tongxinluo capsules (TXL) are widely used in China for treating CCS.ObjectivesTo systematically evaluate the therapeutic effects and safety of adding TXL to Western medical treatment (WM) for CCS.MethodsWe searched PubMed, Cochrane Library, CNKI, VIP, and Wanfang databases up to August 2024 for randomized controlled trials (RCTs) investigating the therapeutic effects and safety of combining TXL with WM compared to WM alone for CCS. Data analyses were conducted using RevMan 5.4 software.ResultsTwenty studies involving 2091 participants were identified. Evidence supports the use of TXL plus WM for reducing angina frequency [SMD −2.50, 95% CI (−3.53, −1.48)], improving seattle angina questionnaire scores (P < 0.05), decreasing nitroglycerin dose [SMD −1.63, 95% CI (−2.26, −1.00)], and shortening angina duration [MD −1.50 min/once, 95% CI (−1.98, −1.02)]. Adding TXL to WM showed a non-significant trend toward reducing myocardial infarction [RR 0.34, 95% CI (0.05, 2.12); NNT = 41] and sudden cardiac death [RR 0.34, 95% CI (0.01, 8.28); NNT = 65]. No increase in adverse events was observed when TXL was added to WM [RR 1.02, 95% CI (0.70, 1.49); NNT = 149].ConclusionsOur review suggests that TXL may offer additional therapeutic benefits for CCS patients and appears to be safe when combined with WM. Further investigations are warranted to confirm the potential impact of adding TXL to WM for CCS.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024499031, PROSPERO (CRD42024499031).